Age as a determinant of phosphate flame retardant exposure of the Australian population and identification of novel urinary PFR metabolites. (January 2015) - Van den Eede, Nele; Heffernan, Amy L.; Aylward, Lesa L.; Hobson, Peter; Neels, Hugo; Mueller, Jochen F.; Covaci, Adrian
Abstract: The demand for alternative flame retardant materials such as phosphate flame retardants and plasticizers (PFRs) is increasing, although little is known of their possible effects on human health and development. To date, no information on the exposure of children or general Australian population to PFRs is available. The objectives of this study were to characterize the average levels and age-related patterns of PFR metabolites in urine in the general Australian population and to identify novel hydroxylated PFR metabolites in urine. Surplus pathology urine samples from Queensland, Australia were stratified and pooled by age and sex (3224 individuals aged 0 to 75 years into 95 pools) according to two different pooling strategies at two different time periods. Samples were analyzed by solid phase extraction and liquid chromatography–tandem mass spectrometry following enzymatic treatment. Nine PFR metabolites were measured in the Australian population, including the first report of a hydroxylated metabolite of TCIPP (BCIPHIPP). Diphenyl phosphate (DPHP), BCIPHIPP and bis(1, 3-dichloro-2-propyl) phosphate (BDCIPP) were detected in > 95% of samples. DPHP, a metabolite of aryl-PFRs, was found in several samples at levels which were one order of magnitude higher than previously reported (up to 730 ng/mL). Weighted linear regression revealed a significant negative association between log-normalized BDCIPP and DPHP levels and age (p < 0.001). Significantly greater levels of BDCIPP and DPHP were found in children's urine compared with adults, suggesting higher exposure to PFRs in young children. BCIPHIPP was identified for inclusion in future PFR biomonitoring studies. Highlights: Levels and age-related patterns of PFR metabolites in pooled urine BCIPHIPP (metabolite of TCIPP) was measured for the first time in human urine. DPHP, BCIPHIPP and BDCIPP were detected in > 95% of samples. DPHP was found in pooled urine up to 730 ng/mL. Significantly greater levels of BDCIPP and DPHP were found in children's urine.